Histopathological Profile In Fatal Yellow Phosphorous Poisoning. Issue 3 (12th October 2018) - Das, Siddhartha; Reddy, Uppalapati Venkata Uma Vamsidhar; Hamide, Abdoul; Badhe, Bhawana; Ravichandran, Muthusamy; Murthy, Abilash Srinivasa
Abstract: Yellow phosphorous (YP) is the toxic form of elemental phosphorous and the chief constituent of firecrackers and rodenticides. In India, the rodenticide paste is frequently used for the suicidal purpose. This study is an autopsy‐based observational study which describes the histopathological features of heart, lungs, liver, and kidney of fatal cases of YP poisoning. The most common autopsy features in the viscera were congestion and petechial hemorrhage. The liver histopathology findings were microvesicular steatosis (68%), hepatic necrosis (62%), macrovesicular steatosis (50%), inflammatory cells (46%), sinusoidal congestion (40%), cholestasis (32%), and toxic hepatitis (18%). Hepatic necrosis ranged from being focal to centrizonal in distribution. Congestion was the most common feature observed in the lungs and the kidney. This is the largest autopsy‐based study on YP poisoning till date. The histopathological features of liver were consistent with YP poisoning whereas the findings of heart, lungs, and kidney were nonspecific in nature.